Forms of nitrogen inputs regulate the intensity of soil acidification - Ze Wang; Tingting Tao; Hu Wang; Ji Chen; Gaston E. Small; David Johnson; Jihui Chen; Yingjun Zhang; Qichao Zhu; Shengmin Zhang; Yantao Song; Jens Kattge; et al. (Global Change Biology, 2023)
Soil acidification induced by reactive nitrogen (N) inputs can alter the structure and function of terrestrial ecosystems. Because different N‐transformation processes contribute to the production and consumption of H + , the magnitude of acidification likely depends on the relative amounts of organic N (ON) and inorganic N (IN) inputs. However, few studies have explicitly measured the effects of N composition on soil acidification. In this study, we first conducted a meta‐analysis to test the effects of ON or IN inputs on soil acidification across 53 studies in grasslands. We then compared soil acidification across five different ON:IN ratios and two input rates based on long‐term field N addition experiments. The meta‐analysis showed that ON had weaker effects on soil acidification than IN when the N addition rate was above 20 g N m −2 year −1 . The field experiment confirmed the findings from meta‐analysis: N addition with proportions of ON ≥ 20% caused less soil acidification, especially at a high input rate (30 g N m −2 year −1 ). Structural equation model analysis showed that this result was largely due to a relatively low rate of H + production from ON as NH 3 volatilization and uptake of ON and NH 4 + by the dominant grass species Leymus chinensis (which are both lower net contributors to H + production) result in less NH 4 + available for nitrification (which is a higher net contributor to H + production). These results indicate that the evaluation of soil acidification induced by N inputs should consider N forms and manipulations of relative composition of N inputs may provide an effective approach to alleviate the N‐induced soil acidification.